TURUT SERTA MELAKUKAN TINDAK PIDANA ABORSI TIDAK SESUAI DENGAN KETENTUAN PASAL 75 AYAT (2) UNDANG-UNDANG KESEHATAN NO 36 TAHUN 2009 (Studi Kajian Putusan : Nomor 482/Pid.Sus/2021/Pn Ckr) - Yanti, Evi; Susanti, Heni (Desiderata Law Review, 2024)
The aim of this research is firstly to find out the consideration of the panel of judges in imposing a crime in the Verdict: Number 482/Pid.Sus/2021/Pn Ckr and secondly to find out the application of Article 149 in conjunction with Article 55 paragraph 1 to 1 of the Criminal Code in the Verdict: Number 482/Pid.Sus/2021/Pn Ckr. This research is normative legal research using a statutory approach and a conceptual approach. The data collection technique was carried out through library research by using the concepts of legal experts which are still related to the basis of the judge's considerations in imposing criminal penalties on perpetrators who participated in carrying out abortions in decision Number 482/Pid.Sus/2021/Pn Ckr. The judge's considerations in imposing a crime on BK were very different from the demands made by the public prosecutor, and in their considerations the panel of judges said that BK had an important role in the abortion of TJ. And the application of Article 194 of the Health Law in conjunction with Article 55 paragraph 1 to 1 of the Criminal Code has been deemed appropriate and fulfills the elements of that article.